A study of job strain and depression in laboratory technicians in Hospital Universiti Sains Malaysia(HUSM) and Kementerian Kesihatan Malaysia(KKM) Hospitals, Kelantan - Nordin, Rusli; Daud, Aziah; Winn, Than; Sadiq, Mohd Ayub (2002)
Job strain is the harmful physical and emotional responses that can happen when there is a conflict between job demands on the employee and the amount of control an employee has over meeting these demands.Job-related depression may often be initiated by high levels of long-term job stress,failure associated with stress-related under-performance, or by life crises.Job-related depression is a clinical illness and the workers should take this seriously.This study is aimed at identifying the psychosocial characteristics of job strain and the relationship between psychosocial job factors and depression in laboratory technicians in HUSM and KKM Hospitals.A cross-sectional study of 84 laboratory technicians in HUSM (response rate 82.4%) and 71 in KKM Hospitals (response rate 89.9%) was conducted from June 2001 till February 2002.Seven KKM Hospitals in Kelantan- Hospital Kota Bharu,Hospital Pasir Mas,Hospital Pasir Puteh,Hospital Tumpat,Hospital Tanah Merah,Hospital Machang,and Hospital Kuala Krai were chosen. Karasek's Job Content Questionnaire (Malay Version) was used as research instrument this study.There were five scales in the questionnaire; two scales were used to define job strain- decision latitude and psychological demands.Results showed that the majority of laboratory technicians in HUSM and KKM Hospitals were classified as passive.However,the proportion of high strain group was the second highest after passive group in both HUSM and KKM Hospitals.The percentage of laboratory technicians in HUSM which was classified as having a high job strain was higher compared to those in KKM Hospitals (33.3% and 26.8%, respectively).The results showed that job insecurity,physical exertion,and total psychological stressor are the significant risk factors of job strain in laboratory technicians in HUSM.However,the significant risk factors of job strain for laboratory technicians in KKM Hospitals are physical exertion and total psychological stressor.Laboratory technicians in HUSM had significantly higher depression as compared to those in KKM Hospitals (59.5% and 39.4%, respectively).We also found significant associations between the risk factors of depression and low social support,and high psychological demands (OR 3 .0, 95o/o CI 1.0-8.8) laboratory technicians in HUSM.However,for laboratory technicians in KKM Hospitals,the significant association was between depression and low social support and low decision authority (OR 9.7, 95o/o CI 1.0-91.1 ).The results of multiple logistic regression analysis revealed that low social support was highly associated with depression in laboratory technicians in HUSM and KKM Hospitals.We therefore conclude that physical exertion and total psychological stressor in the workplace posed significant risk of job strain in laboratory technicians in HUSM and KKM Hospitals.Job insecurity also significantly affected job strain in laboratory technicians in HUSM.A higher proportion of laboratory technicians in HUSM experienced depression compared to those in KKM Hospitals.Low social support positively predicted depression in laboratory technicians in HUSM and KKM Hospitals.In addition, high psychological demand also significantly predicted depression in laboratory technicians in HUSM; however,in laboratory technicians in KKM Hospitals, low decision authority was the significant predictor of depression.